2009
DOI: 10.1197/jamia.m3045
|View full text |Cite
|
Sign up to set email alerts
|

Core Content for the Subspecialty of Clinical Informatics

Abstract: The Core Content for Clinical Informatics defines the boundaries of the discipline and informs the Program Requirements for Fellowship Education in Clinical Informatics. The Core Content includes four major categories: fundamentals, clinical decision making and care process improvement, health information systems, and leadership and management of change. The AMIA Board of Directors approved the Core Content for Clinical Informatics in November 2008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(114 citation statements)
references
References 2 publications
0
111
0
3
Order By: Relevance
“…This work began primarily in the late 1980s 1 and has continued. 2,3 Much of this work has focused on competencies for those who identified themselves as representing different specialties in the field, including biomedical informaticians, 2,4 bioinformaticians, 5 clinical informaticians, 6 and nurse informaticians. 7 Other work has focused on informatics competencies for other practitioners, including medical students, 14 pharmacists, 1 practicing nurses, 15,16 and public health workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work began primarily in the late 1980s 1 and has continued. 2,3 Much of this work has focused on competencies for those who identified themselves as representing different specialties in the field, including biomedical informaticians, 2,4 bioinformaticians, 5 clinical informaticians, 6 and nurse informaticians. 7 Other work has focused on informatics competencies for other practitioners, including medical students, 14 pharmacists, 1 practicing nurses, 15,16 and public health workers.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] As the field continues to evolve, competencies must be adjusted accordingly. Most efforts to define informatics competencies have been regarding those to be demonstrated by informatics professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts by the American Medical Informatics Association to institute a formal medical informatics subspecialty fellowship for physicians [7,8] are well underway. With the support of its sponsoring and sister organizations, it is easy to envision that CIIP certification can become the focus and target of an analagous career training pathway for imaging IT professionals.…”
Section: Future Directionsmentioning
confidence: 99%
“…[18] Although the core content is likely to change as final agreements for requirements are made, it is indicated that the same core content for the clinical informatics subspecialty would also apply to the AIIC. [17] As outlined by Gardner et al the core contact covers four main areas: the fundamentals, clinical decision-making and care process improvement, health information systems, and leadership and management of change.…”
Section: Current State Of Hit Training Programsmentioning
confidence: 99%
“…[17] As outlined by Gardner et al the core contact covers four main areas: the fundamentals, clinical decision-making and care process improvement, health information systems, and leadership and management of change. [18] Each of these areas emphasizes specific content related to clinical informatics (see Table 1). …”
Section: Current State Of Hit Training Programsmentioning
confidence: 99%